Evaluation Of Korkhaus Analysis for Maxillary Crowded Dental Arch in Mosul City - Neam F Agha; Lamiaa A. Hasan; Lara R. Al-Banaa (University of Mosul, College of Dentistry, 2023)
Aims A variety of the indicators have been the proposed method in-order to assist orthodontic diagnosis and treatment planning. This study aimed to appraise the applicability. the index of the Korkhaus to Iraqi persons, and to know if patients that having crowding of teeth have increase in arch length. Material and Methods: The sample consisted of (131) persons their age between (15-20) years, (64) boys and (67) girls, all of Iraqi origin, and live in the centre of Mosul city. All the individuals have Class I molar. relation. The sample consisted of three groups: Normal occlusion group with well aligned teeth (20) boys and (20) girls. Patients had moderate crowding, 2.5 - 4.5mm, (19) boys and (23) girls and severe crowding group, over 5mm, (23) boys and (26) girls. A linear distance was measured on a figure of the scanned study models for upper dental arches by Dimaxis program. statistical analysis with (SPSS) program at the level of P≤0.05 include: comparison between genders using in-depended t-test and, Pearson correlation coefficient among all the variables. Results: The results showed that the measurements (Sum of Incisors, Vertical, Measured Premolar value, measured molar value, Calculated Premolar Value, Calculated Molar Value) in normal occlusion had significantly higher mean Values in males than females. Also, there is a correlation coefficient between the sum of teeth width of four anterior and the posterior arch width which is significant for normal occlusion, but there is no such relation in the most crowding sample. Conclusions: Korkhaus index can be used to determine arch width in Iraqi individuals with normal occlusion, patients with crowded teeth had slight proclination of incisors that is not significant other than normal occlusion. So Korkhaus analysis is considered to be valid for Iraqi class I normal and crowded occlusion.